Ephesians, Philippians, Colossians and Philemon - Johnston, George (London, UK Nelson, 1967)
Includes bibliographical references.
Keywords: Bible. N.T. Ephesians -- commentaries; Bible. N.T. Philippians -- commentaries; Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries